Students' Higher Order Thinking Skills in Environmental Learning: Develop Assessment Based on Green Consumerism - Ilmi Zajuli Ichsan; Diana Vivanti Sigit; Mieke Miarsyah (Universitas Negeri Makassar, 2019)
21st-century learning emphasizes several important abilities, one of which is the ability of Higher Order Thinking Skills (HOTS). This ability can be possessed by students by familiarizing students with HOTS-based questions. The purpose of this study was to develop HOTS-based questions on environmental learning based on green consumerism. The research method used is research and development using Borg and Gall Model. The study was conducted in November 2018 at State Junior High School 1 South Tambun. The validation results show that the assessment on green consumerism-based environmental learning developed has a very valid category according to the experts, and is valid and reliable after measurement. This is because the questions developed are relevant to the current environmental conditions. The results of HOTS male students 44.98 and female students 46.61. The average score of Male and Female 45.79 are still relatively low and need to be improved. The conclusion is that the questions developed have a valid, reliable and appropriate category of use in the process of learning science in junior high school.